PENGARUH PENERAPAN PENDEKATAN KONTEKSTUAL TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Ratri Isharyadi (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to examine the effect of applying the contextual approach to improving students' mathematical problem-solving competencies. Quasi-experimental research used with the design of non-equivalent control group. The population in this study were entire students of class VIII SMP Negeri 3 Lembang. The sampling technique used purposive sampling. Experimental learning class with the contextual approach and control class with the scientific approach. The instrument used is a problem-solving test. Data analysis was done using t-test. The results showed that the improvement of students' mathematical problem-solving skills in the experimental class was better than the students in the control class.